Integrated electrode with strong interface combination, preparation method and application of electrolyzed water to hydrogen production
By introducing a dense transition layer and in-situ growth process into the electrolytic water electrode, the problems of electrode powder loss and activity stability are solved, and efficient and stable electrolytic performance and simplified preparation process are achieved, which is suitable for the application of industrial large-size electrodes.
Patent Information
- Application Number
- CN202411923650.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing electrolytic water electrodes have problems such as severe powder loss, poor activity stability, complex synthesis process and difficulty in preparing large-sized electrodes, which affects the electrolytic efficiency and service life.
An integrated electrode with strong interface bonding was designed. By forming a dense transition layer between the catalytic layer and the substrate, closely combining the catalytic layer and the substrate, overcoming the powder loss problem, and using an in-situ growth process, the catalyst exposes more active sites, improving catalytic activity and stability.
It realizes excellent catalytic activity and long-term catalytic stability of the electrode when electrolysis is performed under high industrial current density, while simplifying the preparation process, reducing costs, and the electrode size is easy to amplify, making it suitable for industrial applications.
Smart Images

Figure HDA0005208681870000011 
Figure HDA0005208681870000012 
Figure HDA0005208681870000021
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrocatalysis, and in particular discloses an integrated electrode with strong interface bonding, a preparation method and an application of water electrolysis to produce hydrogen. Background Art
[0002] Hydrogen is a secondary energy source with a wide range of sources, clean and carbon-free, flexible and efficient, and rich application scenarios. It is also the best choice for achieving large-scale deep decarbonization in transportation, industry, and construction. Hydrogen production by water electrolysis is a green and environmentally friendly hydrogen production technology. Improving water decomposition efficiency and reducing energy consumption are the key to promoting sustainable use of water and energy conversion. Therefore, in the process of industrial production, how to develop low-cost, efficient and stable electrocatalysts to achieve efficient and stable water electrolysis is a problem worth exploring. At present, most of the research on water electrolysis electrodes is based on metal catalysts, powder catalysts or integrated electrodes. Metal-based electrodes generally use low-cost transition metals and their alloys, which can achieve stable electrolysis, but their catalytic activity is not ideal, and it is difficult to further optimize their structure to improve their catalytic activity. Powder catalysts are usually composed of transition metal compounds, and their activity is improved. However, they cannot be used directly, but usually require the use of binders to bind active materials to the substrate, and the binder is prone to failure during the electrolysis process, resulting in the peeling of the active material, which in turn leads to rapid attenuation of the electrode activity, and even causes the entire electrode to fail, seriously affecting the service life of the electrode. Self-supporting integrated electrodes are mainly synthesized through precipitation, water / solvothermal, electrodeposition and other techniques. Although the activity and stability of the electrodes are improved, their synthesis process is relatively complicated, which limits their further application and development.
[0003] Moreover, although a large number of highly active water electrolysis electrode materials have been developed, they have not played a significant role in commercial applications. Most catalysts are only active at low current densities (≤100 mA cm -2 ) to maintain stable electrolysis, and at high current density (≥300mA cm -2 The activity of the electrode (catalyst) rapidly decays and cannot meet the needs of industrial applications. This is mainly due to the low bonding strength between the electrode catalyst and the substrate synthesized using the current process, resulting in a serious "powder loss" phenomenon. In addition, due to the limitations of macroscopic material synthesis methods, the research on integrated electrodes can meet the size requirements of laboratory centimeter-level electrodes, but it is difficult to uniformly prepare meter-level large-size electrodes required for industrial electrolyzers.
[0004] Therefore, the development of a new integrated electrode preparation process with strong interface bonding is crucial to improving the activity and stability of the electrode, which is beneficial to improve the electrolysis efficiency, reduce energy consumption, and extend the service life of the electrode to a certain extent. Summary of the invention
[0005] Even though water electrolysis electrodes have been widely studied, problems such as severe powder loss, unsatisfactory activity stability, and complex synthesis process that make it difficult to scale up still exist, seriously affecting the electrolysis efficiency and service life of the electrodes.
[0006] The present invention is proposed in view of the problems existing in the current water electrolysis electrode, and its purpose is to design the following water electrolysis electrode: there is a dense transition layer between the catalyst layer and the substrate, so that the catalyst layer is closely combined with the substrate, and the problem of electrode powder falling is overcome, so that it not only has excellent catalytic activity but also can maintain long-term catalytic stability even in the case of long-term electrolysis at industrial high current density. In addition, the present invention provides a preparation process for the above-mentioned water electrolysis electrode, which has the characteristics of simple operation, low cost, high consistency and uniformity, easy enlargement of electrode size and batch synthesis, simplifies the preparation process, shortens the electrode preparation time, and reduces the electrode preparation cost. At the same time, the structure and composition of the catalyst layer are adjustable, which provides a new method for improving activity and stability. And this method has universality and can be applied to the synthesis of various transition metal sulfides and various fields.
[0007] In order to solve the above problems, the inventors conducted a lot of research, and the results showed that the presence of the transition layer makes the catalytic layer and the substrate tightly bonded, which is beneficial to promote the enhancement of the interface bonding between the catalytic layer agent and the substrate. At the same time, the process of in-situ growth of the integrated electrode is beneficial to expose more active sites of the catalyst, inhibit the aggregation of active sites, reduce contact resistance, and improve conductivity, thereby improving catalytic activity and stability.
[0008] The present invention proposes an integrated electrode with strong interface bonding, a preparation method and an application of electrolyzing water to produce hydrogen. The electrode is composed of a metal substrate, a transition layer and a catalyst layer, wherein: the metal substrate is composed of at least transition metals such as nickel, molybdenum, iron and their alloys, including: metal foams, nets or felts composed of a series of monovalent, divalent or multivalent transition metals such as nickel, nickel-iron, nickel-cobalt, nickel-copper, nickel-molybdenum or nickel-cobalt-iron; the catalyst layer is composed of corresponding transition metal sulfides, which are in situ grown on the metal substrate, and there is a dense transition layer between the catalyst layer and the substrate. The transition layer has a thickness of 50nm to 10μm and is composed of a mixture of corresponding metals and metal sulfides; the catalyst layer has a thickness of 100nm to 300μm, and its morphology is a porous film, nanoparticles or nanosheet arrays. In addition, the size of the substrate, the sulfur source, the solvent, the reaction time and the reaction temperature can all be adjusted. The present invention can realize the preparation of large-size electrode materials and can be mass-produced. The electrode designed by the present invention has a stable structure and can be used as the cathode and anode of an electrolyzer, and can be directly applied to be used as one or both of the anode and cathode in alkaline water electrolysis or anion exchange membrane water electrolysis to produce hydrogen.
[0009] In one aspect of the present invention, the present invention proposes an integrated electrode with strong interface bonding. According to an embodiment of the present invention, the integrated electrode with strong interface bonding is composed of a metal substrate, a transition layer and a catalyst layer, the metal substrate is at least composed of a transition metal and its alloy, the catalyst layer is composed of a transition metal sulfide, the catalyst layer is in-situ grown on the metal substrate, and there is a transition layer between the catalyst layer and the metal substrate, and the transition layer is composed of a mixture of metal and metal sulfide. The electrode structure is stable and can be used as a cathode and anode of an electrolyzer, and can be directly applied to one or both of the anode and cathode used as alkaline water electrolysis or anion exchange membrane water electrolysis to produce hydrogen.
[0010] According to an embodiment of the present invention, the above-mentioned integrated electrode with strong interface bonding may further include at least one of the following additional technical features:
[0011] According to an embodiment of the present invention, the thickness of the catalytic layer is 100 nm to 300 μm.
[0012] According to an embodiment of the present invention, the morphology of the catalytic layer is a porous film, nanoparticles or nanosheet arrays.
[0013] According to an embodiment of the present invention, the thickness of the transition layer is 50 nm to 10 μm.
[0014] According to an embodiment of the present invention, the transition metal is selected from a series of metal foams, meshes or felts composed of monovalent, binary or multivalent transition metals such as nickel, nickel-iron, nickel-cobalt, nickel-copper, nickel-molybdenum or nickel-cobalt-iron.
[0015] In another aspect of the present invention, the present invention also proposes a method for preparing an integrated electrode with strong interface bonding. According to an embodiment of the present invention, the method comprises:
[0016] placing the metal substrate in an organic solvent and performing a heating treatment to obtain a heat-treated product;
[0017] A sulfur source is injected into the product after the heating treatment to perform mixing treatment and cooling treatment, so as to obtain an integrated electrode with strong interface bonding.
[0018] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:
[0019] According to an embodiment of the present invention, the sulfur source is one or a combination of more than one of mercaptoethanol, sulfur powder, thioacetamide, and thiourea.
[0020] According to an embodiment of the present invention, the sulfur source is mercaptoethanol. The inventors found that the electrode obtained by sulfurization with mercaptoethanol has the highest activity.
[0021] According to an embodiment of the present invention, the organic solvent is a solvent that can dissolve the sulfur source and does not react with the sulfur source.
[0022] According to an embodiment of the present invention, the organic solvent is one or a combination of triethylene glycol, tetraethylene glycol, and triethylene glycol.
[0023] According to an embodiment of the present invention, the sulfur source is a liquid sulfur source, and the volume ratio of the organic solvent to the liquid sulfur source is 20:1 to 1:1.
[0024] According to an embodiment of the present invention, the sulfur source is a liquid sulfur source, and the volume ratio of the organic solvent to the liquid sulfur source is 10: 1. The inventors found that the activity is optimal under this ratio.
[0025] According to an embodiment of the present invention, the sulfur source is a solid sulfur source, and the volume (mL) of the organic solvent and the mass (g) of the solid sulfur source are 20:1 to 5:1.
[0026] According to an embodiment of the present invention, the sulfur source is a liquid sulfur source, and the injection rate of the sulfur source is 0.1 mL / s to 2 mL / s.
[0027] According to an embodiment of the present invention, the sulfur source is a liquid sulfur source, and the injection rate of the sulfur source is 0.5 mL / s. The inventors found that the activity is optimal under this ratio.
[0028] According to an embodiment of the present invention, the sulfur source is a solid sulfur source, and the sulfur source is directly injected.
[0029] According to an embodiment of the present invention, the area (cm 2 ) and the mass (g) of the sulfur source are 1:1 to 1000:1.
[0030] According to an embodiment of the present invention, the area (cm 2 ) and the mass (g) of the sulfur source are 1:1 to 100:1.
[0031] According to an embodiment of the present invention, the area (cm 2 The ratio of the mass (g) of the sulfur source to the mass (g) of the sulfur source is 3: 1. The inventors found that the activity is best under this ratio.
[0032] According to an embodiment of the present invention, the temperature of the heating treatment is between room temperature and the boiling point of the solvent.
[0033] According to an embodiment of the present invention, the mixing treatment time is 1 min to 1 h.
[0034] In yet another aspect of the present invention, the present invention proposes the aforementioned integrated electrode with strong interface bonding or the use of the aforementioned integrated electrode with strong interface bonding in hydrogen production by water electrolysis.
[0035] According to an embodiment of the present invention, the aforementioned integrated electrode with strong interface bonding or the integrated electrode with strong interface bonding described above can be directly used as one or both of the anode and cathode for hydrogen production by alkaline water electrolysis or anion exchange membrane water electrolysis.
[0036] According to the embodiments of the present invention, the present invention has at least one of the following technical effects:
[0037] (1) The present invention designs an electrode for electrolyzing water: a dense transition layer is provided between the catalyst layer and the substrate, so that the catalyst layer is tightly bonded to the substrate, thereby overcoming the problem of electrode powder shedding, and making it have not only excellent catalytic activity but also long-term catalytic stability even under the condition of long-term electrolysis at industrial high current density.
[0038] (2) The present invention provides an electrode preparation process, which has the characteristics of simple operation, short time consumption, low cost, high consistency and uniformity, and easy enlargement of electrode size, simplifies the preparation process, shortens the electrode preparation time, and reduces the electrode preparation cost. At the same time, the structure and composition of the catalytic layer are adjustable, providing a new method for improving activity and stability.
[0039] (3) This method is universal and can be applied to the synthesis of various transition metal sulfides and in various fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0041] Figure 1 The X-ray diffraction (XRD), transmission electron microscopy (TEM), polarization curve (LSV) and long-term potential-time (Et) variation diagram of Example 1;
[0042] Figure 2 It is the scanning electron microscope (SEM) picture of Example 2 and Example 3;
[0043] Figure 3 2 are LSV diagrams of Example 2 and Example 3;
[0044] Figure 4 These are the SEM and LSV images of Example 4. DETAILED DESCRIPTION
[0045] The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0046] The metal substrate is placed in an organic solvent, heated to a certain temperature, and then a sulfur source is quickly injected. After a certain reaction time, the substrate is cooled, taken out, cleaned, and dried to obtain an electrode.
[0047] The metal substrate includes metal foam, mesh or felt composed of a series of monovalent, binary or multivalent transition metals such as nickel, nickel-iron, nickel-cobalt, nickel-copper, nickel-molybdenum or nickel-cobalt-iron. This embodiment takes the nickel mesh substrate as an example.
[0048] The sulfur source includes one or a combination of mercaptoethanol, sulfur powder, thioacetamide, and thiourea. The electrode activity obtained by sulfurization with mercaptoethanol is the highest.
[0049] The organic solvent includes one or a combination of solvents such as triethylene glycol, tetraethylene glycol, and triethylene glycol that can dissolve the sulfur source and do not react with the sulfur source.
[0050] The volume ratio of the organic solvent to the liquid sulfur source was adjusted between 20:1 and 1:1, the volume (mL) of the organic solvent and the mass (g) of the solid sulfur source were adjusted between 20:1 and 5:1, and the activity was best when the volume ratio of the solvent to the liquid sulfur source was 10:1.
[0051] The sulfur source injection rate was adjusted between 0.1 mL / s and 2 mL / s, and the optimal injection rate was 0.5 mL / s. The solid sulfur source was directly injected.
[0052] Area of metal substrate (cm 2 ) and the mass of the sulfur source (g) are adjusted between 1:1 and 100:1, with the optimal ratio being 3:1.
[0053] The reaction temperature is adjusted between room temperature and the boiling point of the solvent;
[0054] The reaction time was adjusted between 1 min and 1 h.
[0055] Example 1
[0056] Based on the above research, 40 mL of triethylene glycol and nickel mesh (1×3 cm 2 ) was added to a container and heated to 200°C in a heating device. At this time, 4 mL of mercaptoethanol was injected and kept at 200°C for 10 minutes. Condensed water was passed during the experiment. After the reaction was completed, the sample was taken out and rinsed with anhydrous ethanol several times, placed in a vacuum oven, and dried at 60°C for 8 hours to obtain the nickel sulfide electrode material (Ni3S2 / NM) grown in situ on the nickel mesh. XRD pattern ( Figure 1 a) shows that Ni3S2 / NM electrode material was successfully synthesized, TEM image ( Figure 1b) shows that a layer of Ni3S2 film is in situ grown on the nickel mesh by in situ sulfidation, and there is a dense transition layer between Ni3S2 and the nickel mesh substrate. LSV curve ( Figure 1 c) It shows that Ni3S2 / NM has good conductivity at a current density of 500 mA cm -2 The overpotential is only 443mV (test conditions: 1.0M KOH electrolyte, room temperature), and at 500mA cm -2 The activity remained unchanged for 1500 hours at high current density ( Figure 1 d) The activity and stability are better than other reported transition metal sulfide electrocatalysts.
[0057] The nickel mesh involved in the present invention is produced by Hebei Chaochuang Metal Mesh Co., Ltd., with a purity greater than 95.5%, a mesh size of 60 meshes, a wire diameter of 0.25 mm, and a mesh opening of 0.17 mm; the manufacturer of mercaptoethanol is Sigma, with a purity of 99%; the manufacturer of triethylene glycol is Beijing Junlibo Biotechnology Co., Ltd., with a purity of 99%. Other sulfur sources and solvents are from Sigma, and transition metal foam is from Jiangsu Jiayisheng Foam Metal Factory, with a purity greater than 99%.
[0058] Example 2
[0059] The other steps are the same as those in Example 1, except that the substrate is changed from nickel mesh to nickel foam. As a result, nickel sulfide nanoparticles (Ni3S2 / NF) uniformly grown on the substrate are obtained. The particle size is small and the morphology is as follows: Figure 2 As shown in a; the prepared sample was applied to electrolyzed water, and the current density reached 500 mA cm -2 The OER overpotential is 560 mV, and the specific polarization curve of the sample is as follows Figure 3 Shown by black line.
[0060] Example 3
[0061] The other steps are the same as those in Example 1, except that the substrate is changed from nickel mesh to nickel iron foam. As a result, a nickel iron sulfide nanosheet array ((Ni,Fe)3S2 / NIF) uniformly grown on the substrate is obtained. The nanosheets are thin and wrinkled, and the gap spacing of the nanosheet array is about 0.8 μm. The specific morphology is as follows Figure 2 b shows that the prepared sample was applied to electrolyzed water to reach 1000 mA cm -2 The current density only requires an OER overpotential of 310 mV. The specific polarization curves of the samples are shown in Figure 3 Shown by red line.
[0062] Example 4
[0063] The other steps are the same as those in Example 3, except that the sulfur source is changed from mercaptoethanol to sulfur powder, thioacetamide and thiourea. As a result, nickel-iron sulfide nanoparticles uniformly grown on the substrate are obtained. The particle size is relatively large, and the specific morphology is as follows: Figure 4 ac; the prepared sample was applied to electrolyzed water to reach 100 mA cm -2 The current densities required OER overpotentials of 309, 293, and 282 mV, respectively. The specific polarization curves of the samples are shown in Figure 4 As shown in d.
[0064] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0065] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. An integrated electrode with strong interface bonding, characterized in that: The electrode is composed of a metal substrate, a transition layer and a catalytic layer, wherein the metal substrate is composed of at least a transition metal and its alloy, the catalytic layer is composed of a transition metal sulfide, the catalytic layer is in-situ grown on the metal substrate, the transition layer exists between the catalytic layer and the metal substrate, and the transition layer is composed of a mixture of metal and metal sulfide.
2. The integrated electrode with strong interface bonding according to claim 1, characterized in that: The thickness of the catalytic layer is 100nm to 300μm; Optionally, the thickness of the transition layer is 50 nm to 10 μm.
3. The integrated electrode with strong interface bonding according to claim 1, characterized in that: The metal substrate is a metal foam, mesh or felt composed of a monovalent, divalent or multivalent transition metal; Optionally, the monovalent, divalent or multivalent transition metal comprises at least one selected from nickel, nickel-iron, nickel-cobalt, nickel-copper, nickel-molybdenum or nickel-cobalt-iron.
4. A method for preparing an integrated electrode with strong interface bonding, characterized in that: include: placing the metal substrate in an organic solvent and performing a heating treatment to obtain a heat-treated product; A sulfur source is injected into the product after the heating treatment to perform mixing treatment and cooling treatment, so as to obtain an integrated electrode with strong interface bonding.
5. The method according to claim 4, characterized in that The sulfur source includes one or a combination of mercaptoethanol, sulfur powder, thioacetamide, and thiourea; Optionally, the organic solvent is a solvent that can dissolve the sulfur source and does not react with the sulfur source; Optionally, the organic solvent is one or a combination of triethylene glycol, tetraethylene glycol, and triethylene glycol.
6. The method according to claim 4, characterized in that The sulfur source is a liquid sulfur source, and the volume ratio of the organic solvent to the liquid sulfur source is 20:1 to 1:1; Optionally, the sulfur source is a solid sulfur source, and the volume (mL) of the organic solvent and the mass (g) of the solid sulfur source are 20:1 to 5:
1.
7. The method according to claim 4, characterized in that The sulfur source is a liquid sulfur source, and the injection rate of the sulfur source is 0.1 mL / s to 2 mL / s; Optionally, the sulfur source is a solid sulfur source, and the sulfur source is directly injected.
8. The method according to claim 4, characterized in that The area of the metal substrate (cm 2 ) and the mass (g) of the sulfur source are 1:1 to 1000:
1.
9. The method according to claim 4, characterized in that The temperature of the heating treatment is between room temperature and the boiling point of the solvent; Optionally, the temperature of the mixing treatment is between room temperature and the boiling point of the solvent; Optionally, the mixing treatment time is 1 min to 1 h.
10. Use of the integrated electrode with strong interface bonding according to claims 1-3 or the integrated electrode with strong interface bonding according to any one of claims 4-9 in hydrogen production by water electrolysis.
Citation Information
Patent Citations
Chemical method for in situ synthesis of platy silver sulphide nano crystal photoelectric film at low temperature
CN101786650A
Preparation method of in-situ synthesis of transition metal oxide / nickel-base sulfide composite material
CN109402660A
Using method and preparation method of metal sulfide modified electrode for electrically reducing carbon dioxide into carbon monoxide
CN110158109A
Self-supporting transition metal sulfide film electrocatalytic electrode and preparation method thereof
CN110512232A
Sand bath reflux preparation method of nickel sulfide electrode material for in-situ growth of foamed nickel
CN114551814A